Mitigating street flooding with permeable structures : A modelling case study - Darrien Yau Seng, Mah; Rosmina, Ahmad Bustami; Frederik Josep, Putuhena; Marelianda, Al Dianty (Prince of Songla University, Thailand, 2022)
This paper describes the modelling efforts of placing a permeable street adjacent to flash-flood-causing urban drain so that overflowing floodwaters from the drain could be absorbed by water storage structure under the street. Three types of permeable structures were included in the modelling with porosities of 23, 63 and 86 % representing low, medium and high storage volumes, respectively. By using the Storm Water Management Model developed by the US Environmental Protection Agency, the properties of the three types of permeable structures were implemented in models imitating a commercial center and its drainage system, as a case study. The permeable street was modelled as part of the drainage system, in contrast to conventional roads rarely modelled as such. Local rainfall patterns were then used with the models of the case study, in which water flow characteristics of the drainage systems with and without the permeable structures were analyzed. The first type that involved conventional pavers and aggregates had the least water detention time of 2 hours. The second type that consisted of modular precast concrete units held the water for 5 hours; and the third type that was cast-in-place concrete tank system held the water longer for 6 hours. The longer the time floodwater is detained within a permeable structure, the better the mitigating effects of the street flooding. The second and third types of structures were more promising than the first type. However, choosing either second type or third type would be a case-by-case decision, considering various factors of the flash flood.